Impairment in social cognition in people with substance use disorders - Piñón-Blanco, Adolfo; Rodrigues, Sonia; Teixeira, Joana; Coutinho, Catia; Faria, Isabela; Murta, Ilda; Tavares, Ana Isabel; Iglesias-Rejas, Luis; Carrera-Machado, Indalecio; Garcia-Caballero, Alejandro; Gutiérrez-Martínez, Olga; Otero-Lamas, Francisco; et al. (Frontiers in Psychiatry, 2025)
IntroductionSubstance use disorders are associated with impairments in various neuropsychological functions. We evaluated potential alterations in social cognition and differences between men and women in individuals with substance use disorders undergoing treatment at Addiction and Dependency Intervention Centers in Portugal.MethodsThe assessment utilized the Ekman 60 Faces Test (EFT), Interpersonal Reactivity Index (IRI), Hinting Task, and Ambiguous Intentions Hostility Questionnaire (AIHQ).ResultsResults showed that 70.2% of participants exhibited social cognition impairments (50% of women and 79.5% of men). Compared to non-clinical populations, individuals with social cognition impairments displayed significant differences in recognizing emotions such as happiness, fear, sadness, disgust, anger, and in the total EFT score. Differences were also observed in the fantasy and personal distress dimensions of the IRI, as well as in hostility, intentionality, and aggression biases on the AIHQ. Slight differences were found between men and women, but were not statistically significant.DiscussionWe discuss the clinical relevance of social cognition alterations and their potential utility in improving diagnostic and therapeutic processes for individuals with substance use disorders.